2008
DOI: 10.1002/sia.2977
|View full text |Cite
|
Sign up to set email alerts
|

Pinhole‐free large‐grained atomically smooth Au(111) substrates prepared by flame‐annealed template stripping

Abstract: High-quality atomically flat substrates are critical for the analysis and imaging of surface-mounted ultrathin films and nanostructures. Here we report significant improvement in the preparation of large areas of atomically smooth Au(111) substrates. A thin layer of gold on silicon is flame-annealed in air and then stripped from the template. The substrates were analyzed with X-ray diffraction and high-resolution atomic force microscopy (AFM). In contrast to the previously reported template stripped gold (TSG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 42 publications
(47 reference statements)
0
30
0
Order By: Relevance
“…We further probed the applicability of our biophysical parameters for accurate base calling using different pH conditions to reversibly perturb the nucleic acid chemistry of DNA nucleobases . We used STS measurements of ssDNA homo‐oligomers on an atomically flat, clean Au(111) substrate prepared with template stripping, after the surface condition was pH adjusted (see a full methods description in the Experimental Section). At each biochemical condition (neutral, basic, acidic), we performed base calling simulations as previously described with LUMO and HOMO parameters only, all nine parameters, and then optimally tuned sets of parameters.…”
Section: Resultsmentioning
confidence: 99%
“…We further probed the applicability of our biophysical parameters for accurate base calling using different pH conditions to reversibly perturb the nucleic acid chemistry of DNA nucleobases . We used STS measurements of ssDNA homo‐oligomers on an atomically flat, clean Au(111) substrate prepared with template stripping, after the surface condition was pH adjusted (see a full methods description in the Experimental Section). At each biochemical condition (neutral, basic, acidic), we performed base calling simulations as previously described with LUMO and HOMO parameters only, all nine parameters, and then optimally tuned sets of parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Deposited molecular films were characterized by atomic force microscopy (AFM), which suggested the formation of high-uniformity SAMs. All molecular films were grown on freshly prepared template stripped Au substrates 37,38 with a surface roughness of 80-150 pm (see Methods section). Averaged roughness, as measured across multiple random areas (ESI- Table S2), showed that SAMs of 1-4 conformally follow the underlying gold surface with comparable roughness.…”
Section: Sam Formation and Characterisationmentioning
confidence: 99%
“…Therefore, the structure and properties of SAMs significantly depend on the substrate. [53] Template stripping can generate surfaces with roughness <1 nm [25], in which technique a glass slide or other solid support is glued to the exposed surface of a metal film deposited on silicon wafer, and then the metal film is peeled from the wafer to expose the surface that had been in direct contact with the wafer. Chen et al (2015) reported a new method, referred to as "remote mechanical annealing (ReMA)" to fabricate ultra-flat Au surface with RMS roughness as low as 0.2 nm [26].…”
Section: Substrates Roughnessmentioning
confidence: 99%